Teaching Neoliberal Emotions through Christian Pedagogies in Fijian Kindergartens. (June 2016) - Brison, Karen J.
Abstract: This article examines a Fijian kindergarten using Accelerated Christian Education (ACE), a curriculum produced by an American corporation for Christian homeschoolers, which combines academic and emotion pedagogies. Pedagogies prompting children to label, reflect on, and control their emotions are popular in American schools and said to develop skills necessary to be self‐directed, risk‐taking entrepreneurs under neoliberalism. In contrast, in Fiji, children educated with the ACE curriculum are told that feeling the correct emotions is a "commitment" and that submitting to authority will benefit everyone. The ACE curriculum appears to turn working‐class American children and children in peripheral countries like Fiji into submissive workers in corporations while middle‐class Euro‐American children are socialized to become innovative entrepreneurs. But further examination shows that Fijian parents and teachers see the curriculum as giving their children the proper skills to succeed in a world outside of Fiji.